Effectiveness of self-care interventions for integrated morbidity management of skin neglected tropical diseases in Anambra State, Nigeria - Chinwe C. Eze; Ngozi Ekeke; Chukwuka Alphonsus; Linda Lehman; Joseph N. Chukwu; Charles C. Nwafor; Eileen Stillwaggon; Anthony O. Meka; Larry Sawers; Joy Ikebudu; Moses C. Anyim; Kingsley N. Ukwaja (BMC, 2021)
Abstract Background Lymphatic filariasis (LF), Buruli ulcer (BU) and leprosy are neglected tropical diseases (NTDs) of the skin co-endemic in some communities in Nigeria. Not enough is known about the effectiveness of integrated morbidity management and disability prevention in people with these conditions. An integrated self-care intervention was carried out for people with these skin NTDs in two endemic communities of Anambra state, Nigeria. The objective of the study was to assess the effectiveness of self-care practices on costs of care, disability status and health-related quality of life. Methods This study utilised a quasi-experimental pre-test/post-test design to assess the effectiveness of the self-care interventions for people affected by NTDs to care for these impairments at home. Data were collected using questionnaires administered at the beginning and at the end of the intervention on monthly cost of morbidity care, and on participants' disability status and their quality of life (QoL). Focus group discussions (FGDs) were held with both the participants and healthcare workers at follow-up. Results Forty-eight participants were recruited. Thirty participants (62.5%) continued the self-care interventions until the end of the project. Of those, 25 (83%) demonstrated improvement from their baseline impairment status. The mean household costs of morbidity care per participant decreased by 66% after the intervention, falling from US$157.50 at baseline to US$53.24 after 6 months of self-care (p = 0.004). The mean disability score at baseline was 22.3; this decreased to 12.5 after 6 months of self-care (p < 0.001). Among the 30 participants who continued the interventions until the end of the project, 26 (86.7%) had severe disability score (i.e. a score of 10-46) at baseline, and the number with severe disability fell to 18 (60%) of the 30 after the intervention. The mean QoL score increased from 45.7 at baseline to 57.5 at the end of the intervention (p = 0.004). Conclusions The 6-month self-care intervention for participants affected by BU, leprosy, or LF led to lower costs of care (including out-of-pocket costs and lost earnings due to morbidity), improved QoL scores, and reduced disability status. Trial registration ISRCTN Registry: ISRCTN20317241 ; 27/08/2021, Retrospectively registered.